Detection of Specific type-A Antigen and Specific Antibody against Avian Influenza virus in Native Duck at Netrokona district of Bangladesh - Islam, MM Mafizul; Akter, Mir Rowshan; Rahman, Md Mostafizer; Haque, Md Atiqul; Uddin, Md Karim; Khan, Md Abu Sayed (Microbes and Health, 2016)
The present study was conducted on unvaccinated native ducks of different age groups to determine specific antibody titer level against Avian Influenza virus (AIV) by indirect Enzyme Linked Immunosorbent Assay (iELISA) and to detect avian influenza type A virus antigen by rapid AIV antigen test kit at Netrokona district of Bangladesh. This study showed that AIV specific antibody positive cases were 78 out of 90 blood serum samples and the highest antibody titer was 2323 and lowest antibody titer was 256. The total 86.67% sera samples were showed positive result. The study showed that 66.66% sera sample were positive against AIV at 3-4 month of aged group and the highest, lowest and mean antibody titer were 1428, 256 and 906.3 respectively. On the other hand 78% sera sample were positive against AIV at 5-6 month aged group and the highest, lowest and mean antibody titer were 1675 , 451 and 1083.6 respectively. The sera sample collected from 7-8 month aged group showed 88.9% positive and the highest, lowest and mean antibody titer were 1857, 578 and 1285.5 respectively. The sera sample collected from 9-10 month of aged group showed 100% positive against AIV and the highest, lowest and mean antibody titer were 197l, 638 and 1571.5 respectively .The sera sample collected from duck of ?11 month aged group were 100% positive against AIV and the highest, lowest and mean antibody titer were 2323, 1423 and 1813.7 respectively. Tracheal and cloacal swabs from ducks with antibody titer more than 1813.778 were tested for the avian influenza type A antigen by Anigen Rapid AIV Ag test kit. The above sample showed 20% positive result. In conclusion it is evident that Avian influenza virus-specific antibody was successfully detected through commercially available Avian influenza virus antibody test kit (ELISA Kit) and the virus induced a significant antibody titer indicating the affecting virus was absolutely AIV.